Early Detection and School Assistance on the Mental Health of Elementary School Children in the Buleleng District: Deteksi Dini dan Pendampingan Sekolah Terhadap Kesehatan Jiwa Anak Sekolah Dasar Pasca Pandemi di Kabupaten Buleleng (JURNAL UNEJ, 2023)
One of the vulnerable groups affected by the COVID-19 pandemic is school children due to the shift to virtual learning activities to prevent the spread of the coronavirus. This has impacted the mental health status of school children, who must adapt to these changes. Schools play a crucial role in improving the mental health status of their students according to their authority. This service activity aims to: 1) Determine the mental health status of students in schools post-COVID-19 pandemic and 2) Enhance the knowledge and understanding of teachers and school staff regarding students' mental health based on early detection data obtained. Methods: The activity consists of two (2) phases: 1) Phase I involves early detection of students' mental health in grades IV, V, and VI using the SDQ-20, and 2) Phase II focuses on providing support and improving the knowledge and understanding of teachers and staff about the mental health of school children, which is measured through pre-tests and post-tests to assess the results of the support. The early detection activity revealed that 16.92% of students were classified in the